Poetry of Politics In The Gulf: Muhammad al-Faytūri And The Iran – Iraq War - Salisu, Mohammed (Al-Ḍād Journal, 2020)
Muhammad al-Faytūri is among the few modern Arabic poets whose works have received considerable academic attention. Nonetheless, the attention has focused on his works on slavery and colonization in Africa. Thus, his poetical works on politics in the Arab Gulf have not received the needed academic attention. This article fills the vacuum by engaging al-Faytūri’s Ya’tī al-‘Āshiqūna Ilaiki, a poetical work that focuses on the Iran-Iraq War. The asymmetric construction of relations between Iran and Iraq relative to racial superiority and regional influence is the furrow that al-Faytūri elects to plough in Ya’tī al-‘Āshiqūna Ilaiki. Situated within the geo-politics of regional counter-hegemony, al-Faytūri’s poetry unveils the politics inherent in the Arab Gulf and the attempt by Iran to dominate the region. The article reveals the poet’s unflinching support for Saddam Hussein and the Iraqi armed forces.